Premixed Combustion of Kapok (ceiba pentandra) seed oil on Perforated Burner - I.K.G. Wirawan; I.N.G. Wardana; Rudy Soenoko; Slamet Wahyudi (International Journal of Renewable Energy Development, 2014)
Availability of fossil fuels in the world decrease gradually due to excessive fuel exploitation. This situations push researcher to look for alternative fuels as a source of renewable energy, one of them is kapok (ceiba pentandra) seed oil. The aim this study was to know the behavior of laminar burning velocity, secondary Bunsen flame with open tip, cellular and triple flame. Premixed combustion of kapok seed oil was studied experimentally on perforated burner with equivalence ratio (φ) varied from 0.30 until 1.07. The results showed that combustion of glycerol requires a large amount of air so that laminar burning velocity (SL) is the highest at very lean mixture (φ =0.36) in the form of individual Bunsen flame on each of the perforated plate hole.  Perforated and secondary Bunsen flame both reached maximum SL similar with that of ethanol and higher than that of hexadecane. Slight increase of φ decreases drastically SL of perforated and secondary Bunsen flame. When the mixture was enriched, secondary Bunsen and perforated flame disappears, and then the flame becomes Bunsen flame with open tip and triple flame (φ = 0.62 to 1.07). Flame was getting stable until the mixture above the stoichiometry. Being isolated from ambient air, the SL of perforated flame, as well as secondary Bunsen flame, becomes equal with non-isolated flame. This shows the decreasing trend of laminar burning velocity while φ is increasing. When the mixture was enriched island (φ = 0.44 to 0.48) and petal (φ = 0.53 to 0.62) cellular flame take place. Flame becomes more unstable when the mixture was changed toward stoichiometry.